Hepatoprotective effects of Artemia salina L. extract against carbon tetrachloride-induced toxicity - Mohammad Ali Mobasher; Akram Jamshidzadeh; Reza Heidari; Ghazal Ghahiri; Nazanin Mobasher (Shiraz University of Medical Sciences, 2016)
The protective effects of Artemia salina L. extract was examined against carbon tetrachloride (CCl4)-induced cell toxicity. In the in vitro model of study, markers such as cell viability, cellular reduced and oxidized glutathione, and lipid peroxidation in HepG2 cells was evaluated. Human liver cancer cell line HepG2 was treated with CCl4 and Artemia salina extract, and markers of hepatotoxicity were investigated. Artemia salina extract showed significant dose-dependent protective effects against the cytotoxicity of CCl4. This extract was able to normalize the levels of GSH, and thiobarbituric acid-reactive (TBARs), which were altered due to CCl4 intoxication in HepG2 cells. As the oxidative stress markers were ameliorated, it might be concluded that Artemia salina extract possesses protective effects probably due to its antioxidant constituents.